2003
DOI: 10.1021/tx025615j
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Are Involved in Arsenic Trioxide Inhibition of Pyruvate Dehydrogenase Activity

Abstract: Arsenite was shown to inhibit pyruvate dehydrogenase (PDH) activity through binding to vicinal dithiols in pure enzyme and tissue extract. However, no data are available on how arsenite inhibits PDH activity in human cells. The IC(50) values for arsenic trioxide (As(2)O(3)) to inhibit the PDH activity in porcine heart pure enzyme preparation and in human leukemia cell line HL60 cells were estimated to be 182 and 2 microM, respectively. Thus, As(2)O(3) inactivation of PDH activity was about 90 times more potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 26 publications
4
72
1
Order By: Relevance
“…Cd (II) may also displace Zn and Ca ions from metalloproteins (Faller et al, 2005;Schutzendubel & Polle, 2002;Stohs & Bagchi, 1995) and zinc-finger proteins (Hartwig, 2001). As (III) has been shown to interact with TRR, pyruvate dehydrogenase and many other proteins (Kitchin & Wallace, 2008b;Menzel et al, 1999;Samikkannu et al, 2003;Wang et al, 2007). Besides, certain proteins may be more susceptible to As (III)-induced protein oxidation than to direct binding of As (III) to critical thiols (Samikkannu et al, 2003).…”
Section: Cadmium and Arsenate Toxicity The Role Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Cd (II) may also displace Zn and Ca ions from metalloproteins (Faller et al, 2005;Schutzendubel & Polle, 2002;Stohs & Bagchi, 1995) and zinc-finger proteins (Hartwig, 2001). As (III) has been shown to interact with TRR, pyruvate dehydrogenase and many other proteins (Kitchin & Wallace, 2008b;Menzel et al, 1999;Samikkannu et al, 2003;Wang et al, 2007). Besides, certain proteins may be more susceptible to As (III)-induced protein oxidation than to direct binding of As (III) to critical thiols (Samikkannu et al, 2003).…”
Section: Cadmium and Arsenate Toxicity The Role Of Oxidative Stressmentioning
confidence: 99%
“…As (III) has been shown to interact with TRR, pyruvate dehydrogenase and many other proteins (Kitchin & Wallace, 2008b;Menzel et al, 1999;Samikkannu et al, 2003;Wang et al, 2007). Besides, certain proteins may be more susceptible to As (III)-induced protein oxidation than to direct binding of As (III) to critical thiols (Samikkannu et al, 2003).…”
Section: Cadmium and Arsenate Toxicity The Role Of Oxidative Stressmentioning
confidence: 99%
“…Arsenic is also shown to inhibit pyruvate dehydrogenase (PDH) activity either via oxidative damage or through binding to vicinal dithiols in both pure enzyme and tissue extract. However, its concentration required to deactivate the enzyme is much lower than what is required for direct binding to thiol groups, suggesting an alternative mechanism (Samikkannu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The decrease in [ATP]i could inhibit Na + /K + ATPase and result in an increase in [Na + ]i, leading to Ca 2+ overload via the Na + /Ca 2+ exchange. The decrease in [ATP]i may also depress SR Ca 2+ -ATPase activity, which causes Ca 2+ overload.…”
Section: Triggered Activities and Electromechanical Alternans During mentioning
confidence: 99%
“…Previous studies have shown cellular Ca 2+ overload, generation of reactive oxygen species (ROS), and decreased intracellular ATP concentration ([ATP]i), [7][8][9] which may provoke triggered activities because of earlyand delayed afterdepolarization (EAD and DAD). In fact, we have observed not only TdP but also non-sustained monomorphic ventricular tachycardias in patients treated with As2O3.…”
mentioning
confidence: 99%